Sociosonic Interventions: Distributed Authorship in Socially Engaged Sound Practices. - Rennie, Tullis (Leonardo Music Journal, 2020)
How do creative sound practices function in the context of socially engaged art? Toward developing a practical methodology, this paper focuses on sound-led projects that stage socially engaged art practice in community settings, including some involving the author. Aesthetics, ethics and politics are employed as interrogative lenses for distributed creative processes. Methods for collaborative art-making that facilitate a balance between these lenses are discussed, with the author further arguing the necessity of artistic "disruption." Such sociosonic interventions are demonstrated to occur most effectively when sound practices challenge the paradigm of unidirectional audial reproduction: rupturing traditional hierarchies of creator and listener.